Hubungan Lama Duduk Terhadap Keluhan Nyeri Punggung Bawah - Ruth O. Hutasuhut; Fransiska Lintong; Jimmy F. Rumampuk (Universitas Sam Ratulangi, 2021)
Abstract: Low back pain is a musculoskeletal disorder that is often found in society. Low Back Pain can cause quality of life to deteriorate and inhibits certain activities. Certain influential factors such as age, gender, Body Mass Index, stress, length of sitting, and posture when doing work. Low Back Pain is a risk to medical students. Purpose of this study was to determine the relationship between sitting time and complaints of low back pain in students of the Faculty of Medicine, Sam Ratulangi University. The research method used is an observational analytic method with a cross-sectional design. Data were collected using a questionnaire and then analyzed using the Pearson Chi-square test. The results showed a p value (p <0.001) between the length of sitting and complaints of low back pain, with a sitting time of 5- 8 hours. In conclusion, there is a significant relationship between sitting time and complaints of low back pain in students of the Faculty of Medicine, Sam Ratulangi University.Keywords: Low Back Pain, prolonged sitting, medical students Abstrak: Nyeri Punggung Bawah (NPB) merupakan gangguan muskuloskeletal yang sering ditemukan dalam masyarakat. NPB dapat menyebabkan kualitas hidup memburuk dan menghambat aktivitas tertentu. Beberapa faktor tertentu yang berpengaruh seperti umur, jenis kelamin, Indeks Massa Tubuh, stres, lama duduk, dan sikap tubuh ketika melakukan pekerjaan. NPB berisiko terjadi pada mahasiswa kedokteran. Tujuan dari penelitian ini adalah untuk mengetahui hubungan lama duduk terhadap keluhan nyeri punggung bawah pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Metode penelitian yang digunakan adalah metode analitik observasional dengan desain potong lintang. Data dikumpulkan menggunakan kuisioner kemudian di analisis menggunakan uji statistik Pearson Chi-square. Hasil penelitian menunjukan p value (p < 0,001) antara lama duduk dan keluhan nyeri punggung bawah, dengan lama duduk 5- 8 jam. Sebagai simpulan, terdapat hubungan bermakna antara lama duduk terhadap keluhan nyeri punggung bawah pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi.Kata Kunci : Nyeri Punggung Bawah, lama duduk, mahasiswa kedokteran